Multi-omics approach to personalised treatment: insights into thrombus-derived exosome regulation in cardiomyocyte ferritinophagy - He, Youfu; Ai, Liqiong; Zhou, Yu; Huang, Jing; Long, Xiangshu; Wu, Qiang (Frontiers in Immunology, 2025)
BackgroundType 1 myocardial infarction (T1MI) is an acute ischemic event triggered by the rupture of a coronary atherosclerotic plaque. The pathogenesis of T1MI is highly complex, involving disturbances in iron metabolism, cell apoptosis, immune activation, and inflammatory responses. In recent years, ferritinophagy, a novel autophagic mechanism regulating iron homeostasis, has attracted increasing attention for its role in cardiovascular diseases. However, its precise involvement in T1MI remains to be fully elucidated. This study aims to systematically analyse the mechanism of ferritinophagy in T1MI and explore its potential connection to immune and inflammatory responses.MethodsExosomes were isolated from coronary thrombi of T1MI patients and subjected to comprehensive transcriptomic profiling. Differentially expressed lncRNAs and mRNAs were validated through functional assays, including RIP, FISH, ChIP, and m6A methylation experiments. Cardiomyocyte models and integrated bulk and single-cell RNA sequencing were used to clarify cellular context and regulatory networks, with particular emphasis on YTHDF family proteins. Bioinformatics analyses, including GO and KEGG, were employed for pathway annotation.ResultsElectron microscopy confirmed the presence of exosomes in coronary thrombi. Thrombus-derived exosomes (TEs) induced pronounced ferritinophagy in cardiomyocytes, evidenced by increased autophagosomes, ROS, apoptosis, and iron overload, with these effects ameliorated by the ferroptosis inhibitor Fer-1. Transcriptomic and functional analyses identified lncRNA FENDRR as highly enriched in TEs, with FENDRR and P53 acting in concert to regulate NCOA4 and system Xc–. Mechanistically, FENDRR directly binds P53, and both upregulate m6A modification in cardiomyocytes, specifically through upregulation of YTHDF1 and downregulation of YTHDF3. Inhibition of either FENDRR or P53 reverses these changes. Single-cell RNA-seq analysis revealed significant upregulation of TP53, NCOA4, and YTHDF1, alongside downregulation of YTHDF3 in macrophages from plaque tissue, linking ferritinophagy, autophagy, and immune-inflammatory responses.ConclusionThis study is the first to reveal the critical role of the “FENDRR–m6A–NCOA4” regulatory axis as a critical mediator of ferritinophagy in T1MI. It also suggests that immune cells may participate in the immune-inflammatory response associated with myocardial injury via ferritinophagy. Our research provides multi-omics evidence of the interaction between iron homeostasis, immunity, and inflammation in T1MI, offering potential therapeutic strategies for targeting ferritinophagy and related RNA modification pathways.